PELAKSANAAN ASAS PENYEWA SEBAGAI TUAN RUMAH YANG BAIK DALAM SUATU PERJANJIAN SEWA MENYEWA RUMAH - RAMINALAI DAKHI (PREMISE LAW JURNAL, 2017)
DOSEN PEMBIMBING:1. Budiman Ginting2. T. Keizerina Devi A3. Edy Ikhsan Leasing contract today becomes a profitable business opportunity although it also has the risk for the damage of the house after the time period of the leasing ends. The damage will, of course, harm the owner. The research used juridical normative method Its nature was descriptive analytic which was aimed to describe, explain, and analyze the problems, and find the correct answers as the solution of the problems. The result of the research shows that the implementation of the principle of a good host as a tenant in a leasing contract is that the tenant has to be responsible to maintain, take care of, and look after the house he is renting. The Panel of Judges’ legal consideration in the Supreme Court’s Ruing No. 2542.K/Pdt/2016 on the dispute in renting a house is that the damage of the house owned by I Nyoman Yudhiawan is because the tenant defaults (breaches of contract) in carrying out the points of the leasing contract, especially on the principle of a tenant who has to be a good host for the house he is renting.Keywords: Tenant, Good Host, House Rent